Geographical reconstruction of the SARS‐CoV‐2 outbreak in Lombardy (Italy) during the early phase. Issue 3 (29th September 2020) - Micheli, Valeria; Rimoldi, Sara G.; Romeri, Francesca; Comandatore, Francesco; Mancon, Alessandro; Gigantiello, Anna; Perini, Matteo; Mileto, Davide; Pagani, Cristina; Lombardi, Alessandra; Gismondo, Maria R.
Abstract: The first identification of autochthonous transmission of SARS‐CoV‐2 in Italy was documented by the Laboratory of Clinical Microbiology, Virology and Bioemergencies of L. Sacco Hospital (Milano, Italy) on 20th February 2020 in a 38 years old male patient, who was found positive for pneumonia at the Codogno Hospital. Thereafter Lombardy has reported the highest prevalence of COVID‐19 cases in the country, especially in Milano, Brescia and Bergamo provinces. The aim of this study was to assess the potential presence of different viral clusters belonging to the six main provinces involved in Lombardy COVID‐19 cases in order to highlight peculiar province‐dependent viral characteristics. A phylogenetic analysis was conducted on 20 full length genomes obtained from patients addressing to several Lombard hospitals from February 20th to April 4th, 2020, aligned with 41 Italian viral genome assemblies available on GISAID database as of 30th March, 2020: two main monophyletic clades, containing 8 and 53 isolates, respectively, were identified. Noteworthy, Bergamo isolates mapped inside the small clade harbouring M gene D3G mutation. The molecular clock analysis estimated a cluster divergence approximately one month before the first patient identification, supporting the hypothesis that different SARS‐CoV‐2 strains had spread worldwide at different times, but their presence became evident only in late February along with Italian epidemic emergence. Therefore, this epidemiological reconstruction suggests that virus initial circulation in Lombardy was ascribable to multiple introduction. The phylogenetic reconstruction robustness, however, will be improved when more genomic sequences are available, in order to guarantee a complete epidemiological surveillance. Highlights: Northern Italy was the most SARS‐CoV‐2 pandemic interested country area. A phylogeographical analysis was conducted to investigate virus entry and circulation in Italy. Two main monophyletic clades were identified, containing 8 and 53 isolates, respectively. The estimated cluster divergence in mid January supported the hypothesis of different viral strains spreading at different times and multiple inputs Lombardy region.